Precision Pharmacotherapy for Obstructive Sleep Apnea: Matching Targeted Drugs to Patient Endophenotypes - Jayoung Oh; Ji Ho Choi (Pharmaceuticals, 2026)
Background: Obstructive sleep apnea (OSA) remains under-treated because continuous positive airway pressure, though efficacious, is frequently limited by poor tolerance and adherence. Long considered a purely anatomical disease refractory to drugs, OSA is now understood as the shared endpoint of four measurable endotypes—a collapsible upper airway, poor pharyngeal dilator-muscle responsiveness, high loop gain, and a low arousal threshold—each a distinct pharmacological target. This review synthesizes the mechanistic rationale and clinical evidence for targeting them. Methods: In this narrative review, we searched PubMed/MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials (January 2000 to February 2026) for randomized trials, meta-analyses, and mechanistic endotyping studies, appraising the evidence narratively. Results: Tirzepatide became the first drug approved for OSA, acting through weight loss to reduce obesity-related mechanical loading, and the noradrenergic–antimuscarinic combination AD109 met its primary endpoint in a pivotal phase 3 trial by targeting dilator-muscle activity independently of weight. Both, however, used AHI-based endpoints in clinically defined rather than endotype-selected populations; AD109’s placebo-corrected effect was modest (−4.0 events/h), and 21.2% versus 3.1% of participants discontinued for adverse events. They are therefore best described as mechanism-informed rather than endotype-validated. Carbonic anhydrase inhibition with acetazolamide or sultiame and selected sedating agents address ventilatory instability and a low arousal threshold, while solriamfetol and pitolisant relieve residual sleepiness. Conclusions: Mechanism-informed pharmacotherapy for OSA is now clinically credible, but scalable bedside endotyping, attention to tolerability, and trait-stratified trials are needed before treatment can be called endotype-guided.